Rare Earth Elements in Andaman Island Surface Seawater: Geochemical Tracers for the Monsoon? - Hathorne, Ed C.; Frank, Martin; Mohan, P. M. (Frontiers in Marine Science, 2020)
The Asian summer monsoon affects the lives of billions of people. With the aim of identifying geochemical tracers for the monsoon related freshwater input from the major rivers draining into the Bay of Bengal and the Andaman Sea we have taken surface seawater samples from various locations spanning the Andaman Islands in 2011 to 2013. In some locations, samples have been taken in March, July and November 2011 thus spanning the seasonal cycle and including different monsoon phases. Generally, the YREE patterns are similar to those reported for offshore samples from the Bay of Bengal and Andaman Sea in January 1997 with seawater normalised REE patterns of most samples are characterised by middle REE enrichments. An enhancement of these middle REE bulges accompany large increases in dissolved REE concentrations from streams and sediment rich areas such as mangrove environments. Conversely, some samples, in particular those taken 1-2 days after heavy rainfall in March 2011, show pronounced REE scavenging accompanied by the preferential removal of dissolved light REEs and by higher Y/Ho ratios. The Nd isotope signature of the remaining dissolved REE phase of these low YREE samples is more radiogenic compared to local rocks and sediments. The time series at a location away from local input sources shows remarkably similar REE patterns and concentrations in March and July. Then in October-November, following the peak in monsoon induced river discharge, the dissolved REE concentrations increase by almost a factor of 2 while Nd isotopes become less radiogenic by 1.5 εNd units. These unradiogenic values are found at the same site in the winter dry season of the following year demonstrating the decoupling of sea surface salinity and Nd. The large sub-annual variability of YREE concentrations and Nd isotopes encountered was likely caused by the conversion of YREE from the dissolved (probably colloidal) pool to the labile particulate fraction. The comparison of unfiltered and filtered sample concentrations reveals the existence of a large labile particulate pool in the BoB and AnS that most likely originates from the massive river sediment fluxes and is instrumental in the seasonal changes observed.